HORTICULTURAL THERAPY REDUCES STRESS IN ELDERLY GRIEVING IN THE MUNA ISLANDS, INDONESIA: HORTICULTURAL THERAPY - Ratna Umi Nurlila; Jumarddin La Fua (STIKes Mandala Waluya Kendari, 2022)
Background: Horticultural therapy is a process through planting, gardening activities, and closeness to nature used as a medium in therapy and rehabilitation programs. Data on the number of older adults in the Muna archipelago in 2018, there are 59 elderly where among them, there are 25 older adults who are suffering from the death of a life partner. Preliminary studies that have been conducted on grieving older people obtained information that they feel grieved because of the loss of a spouse or loss of children so that they think excessive loss causes no enthusiasm in continuing their life that it causes a lazy attitude to eating, lazy to move to hunt for mental tranquility. This study aimed to determine the effect of providing horticultural therapy to reduce stress in the elderly due to grieving in the Muna Islands. Methods: This type of research is analytic, with a Quasi-experimental research design, with data collection methods using pre-test and post-test control group design techniques, with a total population of 25 people and a sample of 20 respondents consisting of 2 groups: the intervention group and the control group, then the data obtained were analyzed using the Paired T-test. Results: The results showed a significant effect of using horticultural therapy on reducing the stress experienced by the elderly who were grieving, where statistical analysis showed a significance value of 0.001 < 0.05, t value = 4.595 >1,383. Conclusion: Horticultural therapy reduces the stress experienced by the elderly who are grieving. Through horticultural therapy, grieving elderly divert their sense of loss in farming activities or plant cultivation activities.